Complement System Part I – Molecular Mechanisms of Activation and Regulation - Merle, Nicolas S.; Church, Sarah Elizabeth; Fremeaux-Bacchi, Veronique; Roumenina, Lubka T. (Frontiers in Immunology, 2015)
Complement is a complex innate immune surveillance system, playing a key role in defense against pathogens and in host homeostasis. The complement system is initiated by conformational changes in recognition molecular complexes upon sensing danger signals. The subsequent cascade of enzymatic reactions is tightly regulated to assure that complement is activated only at specific locations requiring defense against pathogens, thus avoiding host tissue damage. Here we discuss the recent advances describing the molecular and structural basis of activation and regulation of the complement pathways and their implication on physiology and pathology. This article will review the mechanisms of activation of alternative, classical and lectin pathways, the formation of C3 and C5 convertases, the action of anaphylatoxins and the membrane attack complex. We will also discuss the importance of structure-function relationships using the example of atypical hemolytic uremic syndrome. Lastly we will discuss the development and benefits of therapies using complement inhibitors.